Childhood maltreatment and its relation with depression and anxiety among psychiatric patients in Riyadh – KSA - Hajer K Albalawi; Aouab A Khafez; Maha M Alasmari; Qusai M Alsulaiman; Shouq A Alshehri; Yousef A Aldobikhi (Journal of Family Medicine and Primary Care, 2022)
Objectives: Abuse can occur at any stage of childhood leaving an impact on the individual's future mental health. It could be verbal, physical, and emotional. In this research, we focus on determining the correlation of childhood abuse and psychiatric patients with specific aims of identifying the link between depression and anxiety towards child maltreatment. Methods: This cross-sectional study was conducted in a psychiatric clinic among 155 depression and anxiety male and female patients who were randomly selected with age ranging from 20 to 50 plus years. The data were collected by a printed survey distributed manually. Results: Survey of 155 patients showed that (66.5%) raised with both parents. The punishment witnessed by patients in the household was physical (35.5%), emotional (26.5%), and verbal (18.1%). (51.6%) of the patients answered “yes'' when they were asked whether if their caregiver acted in a way scared patients' of getting hurt. Caregivers react to mistakes (X2 = 17.665; P = 0.007), caregiver acted in a way that made patients afraid of getting hurt (X2 = 8.396; P = 0.015). Other variables did not significantly influence anxiety and depression (All > 0.05). Conclusion: Overall, gender and growing with both parents may not affect the psychology of an individual, but maltreatment in childhood (e.g., resorting to physical punishments, constant threats from the caregiver) increases the chances of getting depression/anxiety in adulthood. Regarding our research, childhood maltreatment memories hunt adults in their future leading to psychological damage. Consequently, recognition of childhood maltreatment in family and PHC physicians' clinic might aid in treatment, selection, and management. Aim General Objective: To determine the correlation of childhood abuse with psychiatric patients in Riyadh – Kingdom of Saudi Arabia (KSA). Specific Objective To identify the link between depression and anxiety to childhood maltreatment.To identify the correlation of childhood maltreatment with depression.To identify the correlation of childhood maltreatment with anxiety. Settings and Design: A cross-sectional study consisted of 155 psychiatric patients randomly selected from the University Medical Centre, Riyadh, capital of Saudi Arabia, in January 2020. The samples contained psychiatric patients with depression and anxiety male and female ranging from 20 to 50 plus years. All participants voluntarily participated in this study. Methods and Material: Collection instrument is a self-administered, pre-coded, pre-tested questionnaire devolved mainly for the purpose of this study after consultation from literature and an epidemiologist containing data pertaining to diagnosis, socioeconomic states, and educational level. Statistical Analysis Used: Data were analysed using Statistical Packages for Social Sciences (SPSS) version 23 and Microsoft Excel to generate tables and charts with P < 0.05 considered significant. Data presentation tables are given below. All qualitative variables were presented in terms of numbers and percentages. The relationship between depression and anxiety among the basic demographic data and characteristics of patients during childhood maltreatment had been conducted using Chi-square test. A P < 0·05 was considered statistically significant. Data analyses were performed using SPSS version 21. Conclusion: The study concludes that the presence of maltreatment in childhood (e.g., resorting to physical punishments, constant threats from the caregiver) does in fact increase the chances of acquiring depression or anxiety in adulthood, while other factors (e.g., gender, presence of both parents) do not play a major role compared to maltreatment of the child. The psychological state of children must be well taken care of, and they should be brought up within a supportive healthy environment by a civilized parenting method. Based on our research, childhood maltreatment memories will hunt adults in their future and cause them serious psychological damage. That is why, the recognition of childhood maltreatment in family and primary health care (PHC) physicians' clinic might aid in treatment, selection, and management.